2006
DOI: 10.1038/nmat1779
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent semiconducting polymer systems with low crystallization-induced percolation threshold

Abstract: Blends and other multicomponent systems are used in various polymer applications to meet multiple requirements that cannot be fulfilled by a single material. In polymer optoelectronic devices it is often desirable to combine the semiconducting properties of the conjugated species with the excellent mechanical properties of certain commodity polymers. Here we investigate bicomponent blends comprising semicrystalline regioregular poly(3-hexylthiophene) and selected semicrystalline commodity polymers, and show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
359
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(371 citation statements)
references
References 24 publications
10
359
2
Order By: Relevance
“…26 Furthermore, blends of P3HT with nonconducting crystalline polymers have been shown to force the P3HT into structures capable of conducting when the concentration of P3HT is only 3 wt %. 27 Whether the present Monte Carlo approach is appropriate depends upon whether the morphologies generated by simulated annealing match the local morphology of the device in question. However, the morphologies used are expected to be accurate for many blends.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…26 Furthermore, blends of P3HT with nonconducting crystalline polymers have been shown to force the P3HT into structures capable of conducting when the concentration of P3HT is only 3 wt %. 27 Whether the present Monte Carlo approach is appropriate depends upon whether the morphologies generated by simulated annealing match the local morphology of the device in question. However, the morphologies used are expected to be accurate for many blends.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In order to maintain a good device performance at low content of the conjugated polymer judiciously chosen processing schemes are necessary. Semi‐crystalline matrix polymers such as polyethylenes and isotactic polystyrene (i‐PS) tend to yield superior results provided that the conjugated polymer crystallizes prior to the insulator 5, 13. Notably, bulk‐charge transport can be maintained down to a semiconductor content of only 10 wt%, as observed by Kumar et al using time‐of‐flight photoconductivity measurements 20.…”
Section: Introductionmentioning
confidence: 96%
“…Blends of an organic semiconductor and insulating polymer have been successfully employed for a range of opto‐electronic devices including field‐effect transistors (FETs)5, 6, 7, 8, 9, 10, 11, 12 and bulk‐heterojunction solar cells,13, 14 as well as applications such as elastic conductors15, 16, 17 and organic thermoelectrics 18, 19. In order to maintain a good device performance at low content of the conjugated polymer judiciously chosen processing schemes are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that blends of poly(3-hexylthiophene) (P3HT) with nonconducting commodity polymers can show excellent conduction even at P3HT weight percentages of only a few percent. 25 A starting point for realizing the case n = 2 could be the copolymerization of monomeric units with strongly electron accepting and electron donating properties. The onset of the optical transition for charge transfer in these polymers marks the energy needed to generate free charge carriers and has been made as low as = 0.5 eV.…”
Section: Realization Of Suitable Systemsmentioning
confidence: 99%